2017
DOI: 10.1515/amm-2017-0027
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the steel viscosity and dynamic yield stress for the numerical modelling of casting simulations in the semi-solid state

Abstract: Conditions of some casting processes cause flow of both liquid and semi-liquid metal alloys inside the die cavity. Generally, the continuous casting, squeeze casting or thixoforming could be classified as such processes. Design or optimisation of casting technology using numerical simulations requires knowledge of the rheological properties. The main objective of the experimental work, presented in this publication, is an analysis of the viscosity of 1.2080 (X210Cr12) high carbon steel in liquid and semisolid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…For two Al alloys, it was found that the isostructural yield stress is less than 1/10 of the static value, which was for both alloys about 400 Pa. Comparable experiments have been performed by Solek [73] with high carbon steel, which confirms the above-mentioned findings.…”
Section: Yield Stresssupporting
confidence: 73%
“…For two Al alloys, it was found that the isostructural yield stress is less than 1/10 of the static value, which was for both alloys about 400 Pa. Comparable experiments have been performed by Solek [73] with high carbon steel, which confirms the above-mentioned findings.…”
Section: Yield Stresssupporting
confidence: 73%
“…The movement of liquid steel is described by Navier-Stokes equations resulting from the momentum balance, supplemented with mass conservation equations [1,2,11,44]. They contain both the dynamic viscosity coefficient and the kinematic viscosity coefficient [45][46][47]. Modelling the stress distribution during casting involves the need to declare the rheological parameters i.e., the Young modulus, the Poisson's ratio, yield stress, ultimate yield stress, plastic strain and thermal expansion.…”
Section: Material-related Parametersmentioning
confidence: 99%
“…It included the rheological identification of the selected alloys from a wider perspective with regards to the influence of temperature and the non-dilatational strain rate. Examinations of the rheological properties of the steel alloys carried out as part of the work were used for evaluating the possibilities for applying thixoforming for these alloys [18][19][20][21][22] The methodology of analyzing the rheological properties enabled material tests to be conducted for a broad range of forming parameter values. These parameters substantially impact the material behavior.…”
Section: Rheological Analysis Of High-melting-point Alloys In the Semi-solid Statementioning
confidence: 99%